Pelaksanaan Bimbingan Orang tua dalam Melatih Anak Down syndrome yang Berprestasi Bermain Drum - Warohmah, Annisa; Sopandi, Asep Ahmad (Jurnal Penelitian Pendidikan Khusus, 2022)
This study examines the implementation of parental guidance in training children with Down syndrome who excel in playing the drums. The purpose of this study is to describe how the guidance given by parents to children with Down syndrome who excels and also as a reference for other parents who have children with special needs, especially children with Down syndrome. This study uses qualitative research with a qualitative descriptive approach, using observation, interviews and documentation. The results of this study indicate that as parents of children with Down syndrome have a big and extra responsibility in educating and training children and being able to support and develop the skills of children.